STUDY TO IMPROVE HEAT TRANSFER REDUCTION FOR EXIST BUILDING’S ROOF BY USING LOCAL AVAILABLE MATERIALS - Ahmed Hasan Salih, Ibtisam (Journal of Engineering and Sustainable Development, 2015)
The research is developed to study the impact of structural change makeup for the cover of an exist building’s roof in the city of Baghdad on thermal loads . It included the study of several variables to change the quality of thermal insulation materials for ceilings and the quality of thermal insulation material added, the quality of seven kinds for local material for external packaging ,they are reed, reed without air gap, nylon mat, felt, Jnvas, Jnvas stuffed with sawdust, and hyper HTS and the quality of material used for secondary roof which are plate of gypsum and a hollow plastic plates of (8.5 mm) thickness and (4.7 mm).